For this case we have the following system of equations:
[tex] 3x ^ 2 - 4y ^ 2 = 25
-6x ^ 2 - 2y ^ 2 = 11
[/tex]
We can write a system of equivalent equations.
For this, it is enough to multiply one of the two equations by a scalar.
Multiplying the equation 1 by 2, we have:
[tex] 6x ^ 2 - 8y ^ 2 = 50
[/tex]
Therefore, the new system of equations is:
[tex] 6x ^ 2 - 8y ^ 2 = 50
-6x ^ 2 - 2y ^ 2 = 11
[/tex]
Answer:
A system that is equivalent is:
D) [tex] 6x ^ 2 - 8y ^ 2 = 50
-6x ^ 2 - 2y ^ 2 = 11 [/tex]